Hukum Internasional dan Tantangan Cybersecurity: Keamanan Digital di Era Global - Sechilia Herdianti Nur; Padrisan Jamba (Prosiding, 2025)
International law have an important role in addressing cyber security challenges in the interconnected digital era. Cyber security includes data protection and digital infrastructure that are crucial. Therefore, establishing international cooperation, effective regulation and increasing awareness are the main keys in dealing with complex and ever-evolving cyber. The development of information and communication technology in this digital era has also provided great benefits, but also presents serious challenges in the form of cyber threats.